Cardiopulmonary transplantation. Issue 6 (June 2018) - Parizkova, Barbora; Wright, Gavin
Abstract: The Registry of the International Society for Heart and Lung Transplantation reported 4196 heart transplants and 3812 lung transplants worldwide in 2015. The 100, 000th heart transplant mark has been passed. Heart transplantation is a proven surgical option for selected patients who have advanced heart failure refractory to surgical or medical management. Lung transplantation is the definitive treatment for end-stage lung disease for patients who have failed medical therapy. More than 90% of adult patients presenting for heart transplantation have dilated cardiomyopathy or ischaemic cardiomyopathy. Anaesthetic principles for heart transplantation include full monitoring including transoesophageal echocardiography, cardiostable anaesthesia and cardiac support, and assessment and treatment of pulmonary vascular hypertension. Median survival after cardiac transplantation is 11.9 years. Lung transplantation includes single-lung, double-lung, bilateral sequential single-lung, heart-lung and lobar transplantation. The most common indication is chronic obstructive pulmonary disease, which represents more than one-third of all transplant recipients. Donor criteria are becoming more liberal. Lung transplants may involve cardiopulmonary bypass. Pre-bypass air trapping can compromise cardiac function. Postoperative ventilation management should be guided by pH, not PaCO2 . Thoracic epidural provides optimal analgesia without respiratory depression. Five year survival after lung transplantation is approximately 65%.